Efektivitas Penggunaan Absensi Digital dalam Meningkatkan Ketepatan Waktu Absensi Pegawai Bagian Hukum Sekretariat Daerah Kota Bukittinggi - Rivar Dila Oktavira (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In the Legal Section of the Bukittinggi City Regional Secretariat, the implementation of digital attendance is intended to improve employee discipline, particularly in punctuality in arriving and leaving work. This study aims to assess the effectiveness of digital attendance implementation, identify obstacles encountered, and provide recommendations to support the system's future optimization. Based on in-depth interviews with employees of the Legal Section of the Bukittinggi City Regional Secretariat, the results indicate that the implementation of digital attendance has brought positive changes in attendance discipline. Real-time attendance data makes employees more careful in managing their arrival and departure times, as this system does not impose the same tolerances as manual attendance. However, the reality shows that the implementation of digital attendance does not always run smoothly. Obstacles such as internet network disruptions, device damage, limited employee technical knowledge, and suboptimal individual discipline are still encountered.